Adsorption–photocatalysis synergy of reusable mesoporous TiO2–ZnO for photocatalytic degradation of doxycycline antibiotic - I.J., Ani (2024)
The potentials of mesoporous TiO2–ZnO (3TiZn) were explored on photocatalytic degradation of doxycycline (DOX) antibiotic, likewise the influence of adsorption on the photocatalytic process. The 3TiZn was characterized for physical and chemical properties. Stability, reusability, kinetic and the ability of 3TiZn to degrade high concentration of pollutant under different operating conditions were investigated. Photocatalytic degradation of DOX was conducted at varied operating conditions, and the best was obtained at 1 g/L catalyst dosage, solution inherent pH (4.4) and 50 ppm of DOX. Complete degradation of 50 ppm and 100 ppm of DOX were attained within 30 and 100 min of the reaction time, respectively. The stability and reusability study of the photocatalyst proved that at the tenth (10th) cycle, the 3TiZn is as effective in the degradation of DOX as in the first cycle. This may be attributed to the fusion of the mixed oxides during calcination. The 3TiZn is mesoporous with a pore diameter of 17 nm, and this boosts it potential to degrade high concentration of DOX. It was observed that the adsorption capacity of 3TiZn enhance the photocatalytic process. It can be emphasized that 3TiZn portrayed a remarkable catalyst stability and good potentials for industrial application.